(untitled) - Facts about Finland: Science, trade, culture, industry, history (Keuruu, Finland, 1999)
This book analyses Finland's role as a member of the European Union and examines its relations with the rest of Europe. Leading Finnish experts in their fields discuss the nation's history and constitution, trade and industry, culture and science, and Finnish life.
Keywords: finland - description and travel